Utilization of Instagram Social Media to Disseminate Information Regarding Library Collections - Miawani, Bhara Nurpasma; Irawati, Indira (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This study aims to analyze the use of social media instagram @pustaka.kementan as a means of disseminating information on library collections. This study uses a qualitative method with a case study approach. This research was conducted by observing and analyzing the @pustaka.kementan instagram account based on the category of utilization of Instagram content. The results of the study show that the Ministry of Agriculture Library has made good use of social media, especially Instagram, through @pustaka.kementan. Of the 100 posts in 2023 until April, @pustaka.kementan is mostly used for information/knowledge sharing, then for library marketing or promotion, one of which is regarding library collections. While the category of dissemination of library information and requests for input is still rarely done.